1987
DOI: 10.1037/h0080011
|View full text |Cite
|
Sign up to set email alerts
|

Genital exhibitionism: Courtship disorder or narcissism?

Abstract: The present study contrasted the courtship disorder and narcissism hypotheses of genital exhibitionism. Two offender groups-34 "persistent" exhibitionists and 20 nonviolent nonsex offender controls-were compared on measures of gender identity and sexual and criminal history. The results revealed various things. (1) A surprising number of exhibitionists (41%) were transvestitic but, overall, (2) gender identity was masculine and not significantly different from controls. (3) In partial support of Freund et al.'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…In her 1985 doctoral study, Baker found that the exhibitionists she examined displayed deficits on tasks involving oral word fluency, speech sounds perception and rote verbal learning suggestive of some left frontal-temporal impairment. Genital exhibitionists are an interesting group to explore since they share some common features with rapists as well as paedophiles in that about one-fifth of exhibitionists are aggressive (Rooth, 1973;Lang et al , 1987). Freund, Scher & Hucker (1 983) and Freund & Blanchard (1986) have also noted that exhibitionism, voyeurism, toucherism, frotteurism and preferential rape pattern often co-occur as varying phases of an underlying courtship disorder.…”
Section: Introductionmentioning
confidence: 95%
“…In her 1985 doctoral study, Baker found that the exhibitionists she examined displayed deficits on tasks involving oral word fluency, speech sounds perception and rote verbal learning suggestive of some left frontal-temporal impairment. Genital exhibitionists are an interesting group to explore since they share some common features with rapists as well as paedophiles in that about one-fifth of exhibitionists are aggressive (Rooth, 1973;Lang et al , 1987). Freund, Scher & Hucker (1 983) and Freund & Blanchard (1986) have also noted that exhibitionism, voyeurism, toucherism, frotteurism and preferential rape pattern often co-occur as varying phases of an underlying courtship disorder.…”
Section: Introductionmentioning
confidence: 95%
“…Sexual dysfunctions such as erectile failure and premature ejaculation are reportedly uncommon (Lang et al, 1987). Although some authors believe that the presence of other sexual deviations is uncommon, several studies reveal that exhibitionism may be associated with voyeurism (Langevin, 1983;Langevin et al, 1979;Rooth, 1973); 50% of the exposers studied by Lang et al (1987) had been voyeurs, as were 32% of the 241 exhibitionists described by Freund (1990). Exhibitionism may also be associated with frotteurism and obscene telephone calling (Freund & Watson, 1993).…”
Section: Exhibitionismmentioning
confidence: 92%
“…Contrary to popular belief, exhibitionists do not typically seek to shock or frighten their victims. Most exposers report that they hope the victim will derive enjoyment and sexual arousal from the sight of the exposed penis (Lang, Langevin, Checkley, & Pugh, 1987;Langevin et al, 1979). The desire for sexual intercourse with the victim apparently plays a secondary role because less than one-third of exposers claim that they desire sexual relations with the victim (Langevin et al, 1979).…”
Section: Exhibitionismmentioning
confidence: 96%
See 2 more Smart Citations